Analisis Produktivitas Alat Berat Pada Pekerjaan Timbunan - Dian Febrianti; Zulyaden Zulyaden (Universitas Teuku Umar, 2018)
Heavy equipment plays an important role in terms of speed and acceleration of work. The road improvement project of Suka Makmue Square - the eastern ring road of capital of phase II, funding from OTSUS budget of Nagan Raya Regency with project cost Rp.3.922.503.000, - road length 2475 m The work followed is preferred heap work, B-class aggregate foundation layers, class A aggregate foundation layers. This research uses heavy equipment dump trucks, motor graders, roller vibrators, water tanker trucks. The purpose of the research is to know the productivity of heavy equipment and to know the time needed by heavy equipment to complete the work. The method used is the calculation method manually using the formula productivity. Based on the calculation of productivity at occupation of accumulation using dump truck production per hour 32,4 m/hour, production per day 259.2 m/day with 11 days, 6 days class B class aggregate work, 4 days class A class aggregate work, motor grader production hourly 128,3 m /hour, production per day 1026,43 m3/day with time 3 day, 2 days class B class aggregate work, 1 day class A class aggregate work, vibrator roller production hourly 64,8 m3/hour, production per day 518,4 m3/day with time 6 days, 3 days class aggregate layer work B , 2 days class A class aggregate work, water tankers truck production per hour 16.2 m3/hour, production per day 129,6 m3/day with 21 days, 11 days class B aggregate work, 8 days class A class aggregate work Keywords-productivity, heavy equipment, time of work.